Exploration of electron–vibrational interaction in the 5d states of Eu2+ ions in ABaPO4 (A = Li, Na, K and Rb) phosphors. (28th April 2016) - Nair, Govind B.; Bhoyar, P. D.; Dhoble, S. J.
Abstract: This work reports the theoretical analysis of the electron–vibrational interaction (EVI) in 4f–5d optical transitions of Eu 2 + ions in ABaPO4 (A = Li, Na, K and Rb) systems. The EVI parameters were estimated from the recently reported room temperature photoluminescence results, by employing the spectrum‐fitting method. Parameters such as the Huang–Rhys factor, effective phonon energy, Stokes shift and zero‐phonon line position were estimated and are reported here. The estimated EVI parameters were validated by modeling the emission band and establishing the agreement between the experimental and modeled emission bands. Copyright © 2016 John Wiley & Sons, Ltd.